Diagnostic Accuracy of Serum Ceruloplasmin in the Diagnosis of Pediatric Wilson’s Disease - Sonia, Zannatul Ferdous; Subha, Nahid E; Saha, Dipa; Nayeem, Abu; Rukunuzzaman, Md (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Wilson disease is a autosomal recessive disorder of copper metabolism with diverse clinical manifestation. Early diagnosis is crucial to prevent irreversible damage of liver & brain. Serum ceruloplasmin is one of the major diagnostic parameters for Wilson’s disease. Herein, we evaluate diagnostic value of serum ceruloplasmin level for Wilson disease in children up to age 15 year. Materials & Methods: This case control study was conducted from January 2016 to January 2019 in the department of Paediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Serum ceruloplasmin was measured in 103 WD patients and 58 non-WD patients with other liver disease. Wilson disease was diagnosed using the Leipzig score. Receiver operating characteristics (ROC) curve was used to determine the diagnostic accuracy of serum ceruloplasmin for WD in children. Results: The mean age of WD patients was 9.97±2.5years, male female ratio was 1:1. The mean serum ceruloplasmin level in WD patient was7.76± 4.8, which was significantly lower than that in non-WD patients (34.29±11.17, p=0.00 ).The sensitivity, specificity, and accuracy of a ceruloplasmin level of <20 mg/dl in the discrimination of WD were 99%, 91%, and 96.2% respectively noted. The ROC curve revealed that serum ceruloplasmin level, at a cutoff value of 14.5 mg/dl, had highest AUC value (0.992) with a sensitivity of 89.3% and specificity of 98.3%. Conclusion: Serum ceruloplasmin is one of the sensitive biomarkers for the diagnosis of WD. The cutoff value of serum ceruloplasmin level at 14.5 may provide the highest accuracy for the diagnosis of WD. J Bangladesh Coll Phys Surg 2025; 43: 102-108